Reading Dickens Today: How Contemporary Audiences Interpret Child Welfare in Oliver Twist - Nurhalima, Nurhalima; Hasbi, Muhammad (Universitas Sulawesi Barat, 2025)
Charles Dickens' Oliver Twist offers a powerful critique of institutional child abuse through its depiction of Victorian workhouses, yet how contemporary readers interpret this representation remains underexplored. This study investigates how six Indonesian readers with diverse backgrounds decode Dickens' social critique, applying Stuart Hall's reception theory to analyze their interpretive positions. Through semi-structured interviews and thematic analysis, we found that participants occupied three distinct positions: two demonstrated dominant-hegemonic readings, fully accepting Dickens' humanitarian critique; two adopted negotiated positions, translating Victorian concerns into contemporary child welfare frameworks; and two exhibited oppositional readings, questioning the text's representational authority while advancing alternative interpretations. These findings reveal that interpretive positions correlate with readers' prior knowledge, professional socialization, and cultural contexts rather than emerging randomly. The study demonstrates that classic literature functions not as a vessel for fixed meanings but as contested terrain where historical representations provoke varied contemporary responses. Our analysis contributes to reception studies by empirically demonstrating how readers' social positions shape their engagement with ethically charged literary content, with implications for understanding how canonical texts continue to inform debates about institutional responsibility and child protection.